ICU outcomes and survival in patients with severe COVID-19 in the largest health care system in central Florida. - Eduardo Oliveira; Amay Parikh; Arnaldo Lopez-Ruiz; Maria Carrilo; Joshua Goldberg; Martin Cearras; Khaled Fernainy; Sonja Andersen; Luis Mercado; Jian Guan; Hammad Zafar; Patricia Louzon; et al. (PLoS ONE)
Background Observational studies have consistently described poor clinical outcomes and increased ICU mortality in patients with severe coronavirus disease 2019 (COVID-19) who require mechanical ventilation (MV). Our study describes the clinical characteristics and outcomes of patients with severe COVID-19 admitted to ICU in the largest health care system in the state of Florida, United States. Methods Retrospective cohort study of patients admitted to ICU due to severe COVID-19 in AdventHealth health system in Orlando, Florida from March 11th until May 18th, 2020. Patients were characterized based on demographics, baseline comorbidities, severity of illness, medical management including experimental therapies, laboratory markers and ventilator parameters. Major clinical outcomes analyzed at the end of the study period were: hospital and ICU length of stay, MV-related mortality and overall hospital mortality of ICU patients. Results Out of total of 1283 patients with COVID-19, 131 (10.2%) met criteria for ICU admission (median age: 61 years [interquartile range (IQR), 49.5-71.5]; 35.1% female). Common comorbidities were hypertension (84; 64.1%), and diabetes (54; 41.2%). Of the 131 ICU patients, 109 (83.2%) required MV and 9 (6.9%) received ECMO. Lower positive end expiratory pressure (PEEP) were observed in survivors [9.2 (7.7-10.4)] vs non-survivors [10 (9.1-12.9] p = 0.004]. Compared to non-survivors, survivors had a longer MV length of stay (LOS) [14 (IQR 8-22) vs 8.5 (IQR 5-10.8) p< 0.001], Hospital LOS [21 (IQR 13-31) vs 10 (7-1) p< 0.001] and ICU LOS [14 (IQR 7-24) vs 9.5 (IQR 6-11), p < 0.001]. The overall hospital mortality and MV-related mortality were 19.8% and 23.8% respectively. After exclusion of hospitalized patients, the hospital and MV-related mortality rates were 21.6% and 26.5% respectively. Conclusions Our study demonstrates an important improvement in mortality of patients with severe COVID-19 who required ICU admission and MV in comparison to previous observational reports and emphasizes the importance of standard of care measures in the management of COVID-19.